2014
DOI: 10.1080/03650340.2014.920499
|View full text |Cite
|
Sign up to set email alerts
|

Maize–cowpea intercropping as an ecological approach for nitrogen-use rationalization and weed suppression

Abstract: Small-scale farmers are harshly suffering from high production costs, and so they permanently try to seek and apply the best cheap practices, bearing in mind that no yield losses occur. The objective of this work was to assess the possibility of lowering applied N rate in maize fields associated with less weeds infestation and keeping/boosting productivity. Thus, a field experiment was conducted to evaluate the response of maize yield and associated weeds to N levels (0, 144, 216, and 288 kg N ha −1 ) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…In general, the highest negative values were obtained by intercropping cowpea with TWC 321 hybrid that received 100% mineral fertilization, meanwhile, intercropping cowpea with SC176 hybrid and fertilized by 100% nano urea only had the lowest negative values. Similar results are accordance with Takim (2012) and Saudy (2015) they found that maize was the dominant crop, while cowpea was the dominated one. changes, depending on the properties of NPs.…”
Section: Interaction Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…In general, the highest negative values were obtained by intercropping cowpea with TWC 321 hybrid that received 100% mineral fertilization, meanwhile, intercropping cowpea with SC176 hybrid and fertilized by 100% nano urea only had the lowest negative values. Similar results are accordance with Takim (2012) and Saudy (2015) they found that maize was the dominant crop, while cowpea was the dominated one. changes, depending on the properties of NPs.…”
Section: Interaction Effectssupporting
confidence: 92%
“…On the other hand, the intercropping with TWC maize hybrid produced the lowest gross return (8834 and 9550 LE/fed) and net return (1264 and 1980 LE/fed) when fertilized by nano urea only in first and second seasons, respectively. Economic benefit was higher in maize/cowpea intercropping systems (Takim, 2012;Saudy, 2015;Abdel-Wahab et al, 2016;Olowolaju & Okunlola, 2017).…”
Section: Interaction Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, intercropping maize and cowpea on alternate ridges helped reduce weed [Echinochloa colona (L.) Link., Portulaca oleracea L., Chorchorus olitorius L., and Dactyloctenium aegyptium (L.) Willd.] intensity bỹ 50% as well as improve land use efficiency (Saudy, 2015). In another study, the relay-intercropping of legumes with wheat was evaluated for weed suppression in comparison with the sole wheat crop (Amoss e et al, 2013).…”
Section: Intercropping With Allelopathic Weed Suppressing Plantsmentioning
confidence: 99%
“…Sustainable agriculture calls for limiting use of herbicides either by reducing application rates (Zhang et al, 2013), herbicide rotations, use of selective narrowspectrum products, containing the most ecologically detrimental range of products (Norsworthy et al, 2012) or using alternative soil and crop management methods (Pacanoski et al, 2015;Saudy, 2015). However, development of effective strategic combinations of weed control techniques, where herbicides are a part, remains a major limitation to farmers and their agents in emerging agriculture already beset with poor adoption of herbicide technology.…”
Section: Introductionmentioning
confidence: 99%